2018
DOI: 10.1038/s41586-018-0154-7
|View full text |Cite|
|
Sign up to set email alerts
|

Magnetic edge states and coherent manipulation of graphene nanoribbons

Abstract: Graphene, a single-layer network of carbon atoms, has outstanding electrical and mechanical properties . Graphene ribbons with nanometre-scale widths (nanoribbons) should exhibit half-metallicity and quantum confinement. Magnetic edges in graphene nanoribbons have been studied extensively from a theoretical standpoint because their coherent manipulation would be a milestone for spintronic and quantum computing devices . However, experimental investigations have been hampered because nanoribbon edges cannot be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
231
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(236 citation statements)
references
References 42 publications
2
231
0
3
Order By: Relevance
“…In this regard, an early work on the selfassembly of HBC/perylene diimide dyads could help to understand the peculiar behavior of GNRs [243]. Remarkably, through the bromo-functionalized GNR, which was synthesized by cyclodehydrogenation of the same polyphenylene percursor bearing bromo groups as described above, nitronyl-nitroxide (NIT) radicals were introduced at the edges of the GNRs (177d) [244]. Spin injection from the NIT radicals into the GNR backbone was revealed by electron spin resonance spectroscopy in conjunction with spin density calculations, demonstrating the existence of magnetic edge states of such radical-functionalized GNRs.…”
Section: Edge Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, an early work on the selfassembly of HBC/perylene diimide dyads could help to understand the peculiar behavior of GNRs [243]. Remarkably, through the bromo-functionalized GNR, which was synthesized by cyclodehydrogenation of the same polyphenylene percursor bearing bromo groups as described above, nitronyl-nitroxide (NIT) radicals were introduced at the edges of the GNRs (177d) [244]. Spin injection from the NIT radicals into the GNR backbone was revealed by electron spin resonance spectroscopy in conjunction with spin density calculations, demonstrating the existence of magnetic edge states of such radical-functionalized GNRs.…”
Section: Edge Functionalizationmentioning
confidence: 99%
“…The studies of these N-doped p-HBCs paved the way to GNRs employing pyridinic-N-centers. For example, in 2013, Bronner, Hecht and Tegeder et al [308] reported the Ndoped chevron-type GNR 245 using 4,4′-(6,11-dibromo-1,4diphenyltriphenylene-2,3-diyl)dipyridine (244) as the monomer on Au(111) surface (Figure 54(a)). Du and Feng et al [309] in 2014 revealed the precise structure of N-doped GNR 245 by high-resolution STM.…”
Section: Heteroatom Dopingmentioning
confidence: 99%
“…Although a NV-like spin qubit in graphite is hypothetical, we note that spin qubits have recently been realized as edge states of graphene nanoribbons. 42 We placed a spin qubit in the center of a thin diamond slab of width d or in the central layer of a n-layer graphite (see Supplementary Information) and we considered various nuclear spin concentration. We applied a magnetic field B = 0.05 T along the three-fold axis of the defect; in this direction T 2 attains its maximum value.…”
Section: Effect Of Reduced Dimensionalitymentioning
confidence: 99%
“…However, it introduces disorder and sp 3 defects that restrict charge mobility and reduce the spin relaxation length . Theoretical studies indicate that while spatial confinement and edge engineering can induce the emergence of polarized spins and currents, this is most likely to occur in graphene nanoribbons below a threshold width, with a specific edge geometry or edge functionalization (e.g., graphene nanoribbons functionalized with stable spin‐bearing radical groups) . Therefore, despite its challenges, doping with n‐ or p‐type heteroatoms may be the most practical way to equip graphene with localized spins while maintaining a charge carrier concentration high enough to preserve its conductivity.…”
mentioning
confidence: 99%